Investigation on the mechanical and electrical properties of multiwall carbon nanotubes (MWNCTs) based isotropic conductive adhesives. Issue 4 (4th July 2016) - Durairaj, R.; Pheng, Lim Seow; Ping, Liew Jian
Abstract : Purpose: The purpose of this paper is to characterise the electrical and mechanical properties of multiwall carbon nanotubes (MWCNTs)-based isotropic conductive adhesives (ICAs). The paper also compares the electrical and mechanical performance of MWCNTs-based ICAs with silver flakes and silver nanoparticles-based ICAs. Design/methodology/approach: The ICAs were formulated with dyglycidyl ether bisphenol A epoxy resin and conductive fillers such as silver flakes, silver nanoparticles and MWCNTs. The four-point probe is used to measure the bulk resistivity of the ICAs. Findings: The results from the study showed that the percolation threshold of the MWCNTs-based ICAs is 1.5 Wt.%. At 3 Wt.%, the drop in bulk resistivity is lower than the conventional ICAs. The addition of silver nanoparticles increased the overall bulk resistivity of the system. The mechanical properties improved with the introduction of carbon nanotubes into the silver flakes–epoxy system. Practical implications: The results from bulk resistivity and mechanical properties of the MWCNTs could help to formulate MWCNTs-based ICAs with optimum weight fraction. Originality/value: The paper demonstrates that the addition of MWCNTs to the silver-based ICAs will enhance their mechanical and electrical conductivity. In addition, the optimum weight percentage is also determined, which shows a bulk resistivity value lower along with improved mechanical property with the conventional ICA system.